Mapping the literature on thermal tourism: A bibliometric and content analysis - AlQaifi, Faten; Tengilimoglu, Dilaver; Aras, Ilknur Arslan (Journal of Tourism Management Research, 2025)
This study explores and maps the existing literature on thermal tourism to provide comprehensive insights and inform future research directions. The research design is based on a bibliometric analysis of 48 documents published between 2013 and 2023 and indexed in the Web of Science database. Data were processed and visualized using Microsoft Excel and Bibliometrix, followed by a content analysis of 42 English-language articles to capture thematic developments in the field. The findings indicate that, despite a temporary decline during the COVID-19 pandemic, publications on thermal tourism have shown strong growth and recovery, with an annual growth rate of 46.65%. The most significant contributions originated from Portugal, China, Spain, Taiwan, Turkey, and Japan, with research disseminated across 37 journals. Four central themes were identified: (1) tourist behaviors and satisfaction, (2) demand and motivations, (3) quality and resource management, and (4) strategic and sustainable development. Among these, tourist behaviors and satisfaction emerged as the most prominent research area, representing 38.10% of the analyzed literature. This paper addresses a gap in the literature by mapping the knowledge landscape in the relatively underexplored field of thermal tourism, highlighting its growth potential and proposing a future research agenda. The practical implications suggest that recognizing these trends and themes can help policymakers, industry stakeholders, and academics develop strategies to enhance sustainable practices and expand opportunities in thermal tourism.